2016
DOI: 10.1038/srep26821
|View full text |Cite
|
Sign up to set email alerts
|

RhBMP-2 Activates Hippo Signaling through RASSF1 in Esophageal Cancer Cells

Abstract: Despite that recombinant human bone morphogenetic protein-2 (rhBMP-2) has been reported as a stimulatory effecter of cancer cell growth because of its characteristic like morphogen, the biological functions of rhBMP-2 in human esophageal cancer cells are unknown. The purpose of this study was to investigate whether rhBMP-2 has an inhibitory effect on the growth of human esophageal squamous carcinoma cells (ESCC). RhBMP-2 significantly inhibited proliferation of ESCC cells in a dose-dependent manner in the MTT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…These previous results are conspicuously consistent with our present results. Our current study surprisingly showed that complex formation via disruption of AKT-RASSF1 interaction [41]. Another report showed that canonical BMP signaling induces expression of RUNX3 and BMP2/4-induced RUNX3 suppress tumor growth through repression of c-Myc promoter activity via binging RUNXbinding elements in c-Myc promoter [25].…”
Section: Discussionsupporting
confidence: 51%
“…These previous results are conspicuously consistent with our present results. Our current study surprisingly showed that complex formation via disruption of AKT-RASSF1 interaction [41]. Another report showed that canonical BMP signaling induces expression of RUNX3 and BMP2/4-induced RUNX3 suppress tumor growth through repression of c-Myc promoter activity via binging RUNXbinding elements in c-Myc promoter [25].…”
Section: Discussionsupporting
confidence: 51%
“…TAZ/YAP was also demonstrated to regulate BMP4 expression in zebrafish [69], and indirectly crosstalk with BMP2 signaling pathway [70]. Additionally, BMP2 has been suggested to induce cytoplasmic retention of YAP [71]. Thus, increasing data suggest crosstalk between BMPR and Hippo signaling pathways.…”
Section: Discussionmentioning
confidence: 96%
“…Interestingly, MST1 could negatively regulated Akt activity and thereby promote GSK3β [25, 26], which could activate p21 [27]. So, the repression of p21 after KCTD11 knock-down in Huh7 could be a result of up-regulated MST1/GSK3β.…”
Section: Resultsmentioning
confidence: 99%